Seasonal Patterns of Peak Expiratory Flow Rate in Young Healthy Individuals - Mahotra, Narayan Bahadur; Chaudhary, Sonam; Pradhan, Sait (Journal of Karnali Academy of Health Sciences, 2023)
Background: The seasonal changes are associated with changes in pulmonary functions including Peak Expiratory Flow Rate (PEFR). These changes are different among different population and location. This study thus aims to evaluate the seasonal variations in PEFR among healthy young individuals in Kathmandu. Methods: A comparative study was carried out among 60 undergraduate medical students of Maharajgunj Medical Campus in the department of Clinical Physiology. The students were selected by convenient sampling technique and after obtaining the informed consent, the PEFR was recorded with the help of Wright’s peak flow meter with proper training. The PEFR was recorded two times i.e. morning and daytime hours in winter season (JanuaryFebruary) 2023 and also in same daily hours of summer season (May-June) 2023 in the same participants. The data were analyzed using SPSS-16 version and the paired T test was used to compare the mean changes in PEFR in winter and in summer seasons. Results: The PEFR in summer morning (499.50±89.50 L/min) was recorded higher than in winter morning (487.50±86.09 L/min) among total participants and also in male participants (567.33±69.34; 550.83±69.58) which was statistically significant with P value <0.05. Similarly, the PEFR in summer daytime (505.08±88.85 L/min) was comparatively more than in winter daytime (491.27±92.07 L/min) which was statistically significant among all participants with P value <0.05. The PEFR in the winter and summer seasons of male participants and in the summer of total participants showed the existence of diurnal variation which was statistically significant. Conclusions: There is seasonal variation as well as diurnal variations of PEFR. So, the clinicians should be aware that the PEFR recorded in winter season and in the morning time might be less than that recorded in the summer and at the daytime respectively.